Diseño e implementación de un sistema de desalinización a pequeña escala alimentado por medio de un sistema solar fotovoltaico (2020)
This document presents a structural and energy design proposal for a small-scale desalination system powered by photovoltaic solar energy. Each of the components is detailed, justifying their choice and the present value cost analysis is included.--Taken from the Degree Document Format.